2022
DOI: 10.3390/ijerph19148785
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Change Simulation in Rapid Urbanizing Regions: A Case Study of Wuhan Urban Areas

Abstract: Until now, few studies have used the mainstreaming models to simulate the land use changes in the cities of rapid urbanizing regions. Therefore, we aimed to develop a methodology to simulate the land use changes in rapid urbanizing regions that could reveal the land use change trend in the cities of the regions. Taking the urban areas of Wuhan, a typical rapid urbanizing region in China, as the study area, this study built a Markov chain–artificial neural network (ANN)–cellular automaton (CA) coupled model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…As Wuhan has grown and developed, the central urban areas have experienced significant land cover changes, with the conversion of green spaces, wetlands, and agricultural lands into built-up areas [67]. This process has led to the degradation of natural habitats, reduction in biodiversity, and increased environmental pollution [68]. Moreover, the high concentration of population and industrial activities in the urban core has placed additional pressure on the local ecosystem, contributing to the lower EQ in these areas [69].…”
Section: Spatial Patterns Of Eq and Causal Analysismentioning
confidence: 99%
“…As Wuhan has grown and developed, the central urban areas have experienced significant land cover changes, with the conversion of green spaces, wetlands, and agricultural lands into built-up areas [67]. This process has led to the degradation of natural habitats, reduction in biodiversity, and increased environmental pollution [68]. Moreover, the high concentration of population and industrial activities in the urban core has placed additional pressure on the local ecosystem, contributing to the lower EQ in these areas [69].…”
Section: Spatial Patterns Of Eq and Causal Analysismentioning
confidence: 99%
“…Additionally, scholars [41] proposed the factor of merit (FoM) as an alternative measure to evaluate simulation accuracy. FoM relies solely on the number of varying cells in the simulated process and offers a more robust assessment of simulation accuracy [13,16] . Building upon this, in this study, historical data was used for simulation, with the 2018 dataset serving as the initial input and the 2021 dataset used for verifying the validity of the CA model [1] .…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…The rapid and intense land use changes often observed in new areas within cities necessitate close monitoring and thorough understanding. When utilizing CA models for geographic simulation, researchers have found that the expansion of urban areas is influenced by a series of driving factors, including topographic conditions, transportation factors, and socio-economic development [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations